Translation And Accountability In Electronic Procurement (E- Procurement) Of Goods And Services - Muhammad Rafli; Tengku Aisyah Rahmi Zulmi; Cahya Nafasya; Salsa Liza Nabilla; Neng Sri Wardhani (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this research is to find out how translation and accountability are in the procurement of goods and services. The method used in this research is a literature study with a narrative review model. The research method used is a qualitative research method with the data source used in the form of secondary data obtained from several international journals, national journals, articles and previous research. The results of this research are that the implementation of translation and accountability in electronic procurement of goods and services is very good. This can be seen from the ease of accessing auctions online via the page provided and the responsibilities are also very clearly reported.